2022
DOI: 10.1101/2022.03.04.482958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Listeria monocytogenes gene essentiality under laboratory conditions and during macrophage infection

Abstract: The Gram-positive bacterium Listeria monocytogenes occurs widespread in the environment and infects humans when ingested along with contaminated food. Such infections are particularly dangerous for risk group patients, for whom they represent a life-threatening disease. To invent novel strategies to control contamination and disease, it is important to identify those cellular processes that maintain pathogen growth in- and outside the host. We here have applied transposon insertion sequencing (Tn-Seq) to L. mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 131 publications
(179 reference statements)
0
1
0
Order By: Relevance
“…In B. subtilis , WalRK also regulates the expression of genes involved in WTA biosynthesis and export (Howell et al, 2003). The regulon of the WalRK system has not yet been determined for L. monocytogenes , however, it was shown that the system is essential (Fischer et al, 2022). Inactivation of WalRK usually leads to cell death of wildtype cells due to loss of peptidoglycan hydrolase activity, however, cell death could be prevented by the inhibition of peptidoglycan biosynthesis (Salamaga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In B. subtilis , WalRK also regulates the expression of genes involved in WTA biosynthesis and export (Howell et al, 2003). The regulon of the WalRK system has not yet been determined for L. monocytogenes , however, it was shown that the system is essential (Fischer et al, 2022). Inactivation of WalRK usually leads to cell death of wildtype cells due to loss of peptidoglycan hydrolase activity, however, cell death could be prevented by the inhibition of peptidoglycan biosynthesis (Salamaga et al, 2021).…”
Section: Discussionmentioning
confidence: 99%